An updated view of plasmid conjugation and mobilization in Staphylococcus. (3rd July 2016) - Ramsay, Joshua P.; Kwong, Stephen M.; Murphy, Riley J.T.; Yui Eto, Karina; Price, Karina J.; Nguyen, Quang T.; G. O'Brien, Frances; B. Grubb, Warren; W. Coombs, Geoffrey; Firth, Neville
ABSTRACT: The horizontal gene transfer facilitated by mobile genetic elements impacts almost all areas of bacterial evolution, including the accretion and dissemination of antimicrobial-resistance genes in the human and animal pathogen Staphylococcus aureus . Genome surveys of staphylococcal plasmids have revealed an unexpected paucity of conjugation and mobilization loci, perhaps suggesting that conjugation plays only a minor role in the evolution of this genus. In this letter we present the DNA sequences of historically documented staphylococcal conjugative plasmids and highlight that at least 3 distinct and widely distributed families of conjugative plasmids currently contribute to the dissemination of antimicrobial resistance in Staphylococcus . We also review the recently documented "relaxase- in trans " mechanism of conjugative mobilization facilitated by conjugative plasmids pWBG749 and pSK41, and discuss how this may facilitate the horizontal transmission of around 90% of plasmids that were previously considered non-mobilizable. Finally, we enumerate unique sequenced S. aureus plasmids with a potential mechanism of mobilization and predict that at least 80% of all non-conjugative S. aureus plasmids are mobilizable by at least one mechanism. We suggest that a greater research focus on the molecular biology of conjugation is essential if we are to recognize gene-transfer mechanisms from our increasingly in silico analyses.